2006
DOI: 10.1200/jco.2005.05.0104
|View full text |Cite
|
Sign up to set email alerts
|

Invisible Barriers to Clinical Trials: The Impact of Structural, Infrastructural, and Procedural Barriers to Opening Oncology Clinical Trials

Abstract: There are numerous opportunities to remove nonvalue-added steps and save time in opening clinical trials. With increasing numbers of new agents, fewer domestic principal investigators, and more companies off-shoring clinical trials, overcoming such barriers is of critical importance for maintenance of core oncology research capabilities in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
133
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 5 publications
7
133
0
Order By: Relevance
“…Study start-up has been examined in more detail in oncology clinical trials. [12][13][14] These studies also observed that administrative processes, including review of a protocol by multiple IRBs, lengthen study start-up times. Some institutions require completion of the contract execution process before submission of a protocol to their local IRB.…”
Section: Adherence and Retentionmentioning
confidence: 97%
“…Study start-up has been examined in more detail in oncology clinical trials. [12][13][14] These studies also observed that administrative processes, including review of a protocol by multiple IRBs, lengthen study start-up times. Some institutions require completion of the contract execution process before submission of a protocol to their local IRB.…”
Section: Adherence and Retentionmentioning
confidence: 97%
“…1 The slow development of protocols, redundant scientific and ethical reviews, and protocol requirements that hinder enrollment contribute to the inferior conduct of clinical trials in academic centers. [2][3][4] In 2006, the Clinical and Translational Science Award (CTSA) program of the National Institutes of Health (NIH) was developed to support a national consortium of biomedical research institutions to accelerate progress in clinical research. The NIH subsequently requested proposals for work that would improve processes related to the development, approval, activation, enrollment, and completion of clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Division of Pulmonology, Department of Pediatrics, University of North Carolina at Chapel Hill, Chapel Hill, NC, USA; 2 Cystic Fibrosis Therapeutics Development Network Coordinating Center, Seattle Children's Research Institute, Seattle, WA, USA; 3 Cystic Fibrosis Foundation, Bethesda, MD, USA; 4 University of Pittsburgh, Pittsburgh, PA, USA; 5 The Dartmouth Institute for Health Policy and Clinical Practice, Geisel School of Medicine at Dartmouth, Dartmouth-Hitchcock Health Care System, Lebanon, NH, USA; 6 University of Washington, Seattle, WA, USA.…”
mentioning
confidence: 99%
“…It had also commissioned Dr. David Dilts to undertake a systems analysis of clinical trial approval and implementation to determine where the bottlenecks to clinical trial delivery were most acute [3]. Contract negotiations could take more than a year, and there was no difference in the time needed to finalize contracts by phase of study.…”
Section: Improved Delivery Of Cancer Drug Clinical Trialsmentioning
confidence: 99%